PERSEPSI MILENIAL TERHADAP PODCAST HORROR DO YOU SEE WHAT I SEE - Miranda Devi Muslimah; Nurliah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
The development of technology that is currently widely used by millennials is podcasts which are currently increasingly trending among millennials. One of the most popular podcasts in Indonesia is the Do You See What I See podcast, which brings the horror genre as its main topic. The purpose of this study is to analyze and describe millennial perceptions in perceiving content that is broadcast in the Do You See What I See podcast based on indicators of perception formation. The methodology in this research is qualitative with a descriptive approach. The data collection technique is triangulation. There are 9 informants obtained through purposive sampling technique based on predetermined criteria. Meanwhile, data processing in this study used techniques from Matthew and Michael Huberman. Based on the results of the study, the majority of listeners of the Do You See What I See podcast are aged 22-30 years. The listener's perception of the Do You See What I See podcast itself is that listeners begin to accept the existence of the podcast, then listeners begin to understand the content of the content shared in the podcast. The majority of listeners' assessment of the Do You See What I See podcast is positive. So in conclusion, the listener's perception of the Do You See What I See podcast is good and positive.